Diabetic Retinopathy as a Risk for Primary Open Angle Glaucoma: Doi: 10.36351/pjo.v39i3.1486 - Khalil, Iqra; Kiran, Ayesha; Haider, Sajjad; Kanwal, Bushra (Pakistan Journal of Ophthalmology, 2023)
Purpose: To evaluate diabetic retinopathy as a risk factor for open-angle glaucoma. Study Design: Case control study. Place and Duration of Study: Munawar Memorial Hospital Chakwal from December 2021 to April 2022. Methods: A sample of 206 eyes of 103 diabetic patients, 40 to 65 years of age and either gender were included in the study. The eyes were divided into two groups on the basis of presence and absence of diabetic retinopathy. Data included age, gender, visual acuity, intraocular pressure, type, and duration of diabetes mellitus. Fundus examination was carried out using a 90 Diopters lens. Diabetic retinopathy was graded according to the early treatment diabetic retinopathy scale (ETDRS). Primary open angle glaucoma was diagnosed on the basis of optic nerve head changes, defective visual field and raised intraocular pressure. Data was analyzed by IBM SPSS Statistics for Windows, Version 20.0. Results: Of 103 subjects 52 subjects were male and 51 were female. Of the 206 eyes of 103 subjects, 100 eyes had no signs of diabetic retinopathy while 106 eyes had signs of diabetic retinopathy. Fifty six eyes had primary open angle glaucoma. Chi-square and a multivariate regression model were used for analysis. The odds ratio of diabetic retinopathy for primary open angle glaucoma was 1.50. Conclusion: In conclusion, Diabetic retinopathy was found to be a significant risk for developing primary open angle glaucoma in addition to other contributing factors like age, duration of diabetes mellitus, increased intraocular pressure, Ocular Perfusion pressure, and cup disc ratio.